Does prepectoral placement delay adjuvant therapies compared to retropectoral immediate implant-based breast reconstruction? A retrospective analysis - Zinner, Gauthier; Martineau, Jerome; Lam, Giang-Thanh; Tremp, Mathias; Giordano, Salvatore; Dong, Edward T. C.; Kalbermatten, Daniel F.; Oranges, Carlo M. (ELSEVIER SCI LTD, 2025)
Background: Prepectoral (PP) immediate implant-based breast reconstruction (IBBR) is becoming increasingly popular compared to retropectoral (RP) reconstruction. This study compares the timing of administration of different adjuvant therapy (ATs) after PP or RP IBBR.
Patients and methods: A monocentric retrospective analysis was conducted on patients undergoing mastectomy and IBBR from January 2018 to December 2023. Preoperative characteristics, mastectomy procedure type, PP or RP implant placement, postoperative outcomes, AT type, and time between surgery and AT administration were collected and analyzed.
Results: 167 patients (206 breasts) were included. 123 underwent PP IBBR and 44 RP IBBR. The mean time between surgery and first AT administration was similar in the PP group (45.7 days, SD 39.3) compared to the RP group (37.4 days, SD 33.1) (p-value 0.2100). No significant differences were found in the timing of endocrine therapy (ET), chemotherapy (CT), or radiotherapy (RT) initiation between the PP and RP groups. Patients with seroma had a delayed initiation of CT (83.67 days, SD 123.7) versus those without seroma (42.1 days, SD 29.7) (p-value 0.0298).
Conclusions: The average time between surgery and administration of the first AT following PP IBBR was similar compared to RP IBBR. Postoperative seromas were associated with delayed CT in the overall population. (c) 2024 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creative- commons.org/licenses/by/4.0/).